The Foxfire book : hog dressing; log cabin building; mountain crafts and foods; planting by the signs; snake lore, hunting tales, faith healing; moonshining; and other affairs of plain living. - Wigginton, Eliot (Doubleday, 1972)
Interviews and essays describe the way of life and crafts of pioneer America still surviving in the Appalachian region.